Discourse on the Value of the Humanities in Lithuania: for the Sake of This Land, or for the People’s Well-Being? - Kirtiklis, Kęstas (Sociologija. Mintis ir veiksmas, 2019)
The present paper deals with the polemics concerning the importance of the humanities in Lithuania. The arguments provided by the critics – natural scientists, politicians, businessmen, and general public opinion – are reconstructed from the humanities perspective, i.e. from the texts where humanitarians try to respond to them. The arguments for the value of the humanities, formed by prominent scholars Darius Kuolys, Alvydas Jokubaitis, and Viktorija Daujotytė are also presented. The paper argues that this debate is essentially a clash of two axiological positions. The critics of the humanities occupy the position of axiological collectivism and claim that the humanities must provide a measurable impact on human communities – a nation, society, or business corporation. Humanitarians, in their turn, adopt the perspective of axiological holism and argue the value of the humanities for the nation or the state as entities exceeding the sum of their parts. The paper suggests that the turn toward axiological individualism might be a way to escape the deadlock that these polemics have reached. The title of this article paraphrases two lines of the Lithuanian National Anthem.
Keywords: humanities; arguments for the values of the humanities; the impact of the humanities; axiological holism; axiological collectivism; Lithuanian studies